Observations on the Study of Byzantine Hagiography in the Last Half-Century or Two Looks Back and One Look Forward - Ševčenko, Ihor (Université d'Ottawa | University of Ottawa, 1995)
Lecture presented in a series for the Canadian Institute for Balkan Studies.